Prospects of X‐ray photoemission electron microscopy at the first beamline of the Polish synchrotron facility 'Solaris'. (3rd July 2015) - Ślęzak, M.; Giela, T.; Wilgocka‐Ślęzak, D.; Spiridis, N.; Ślęzak, T.; Zając, M.; Kozioł‐Rachwał, A.; Socha, R. P.; Stankiewicz, M.; Warnicke, P.; Pilet, N.; Raabe, J.; et al.
<x xml:space="preserve">Abstract</x> The synchrotron radiation facility 'Solaris' is currently being built in Krakow, Poland. The first experimental beamline at Solaris will use bending magnet radiation and two exchangeable end stations: a spectroscopic X‐ray photoemission electron microscope and a soft X‐ray absorption spectroscopy chamber. We present the beamline specifications and exemplary results obtained with our end station microscope, which (in statu nascendi of Solaris) has been operated at the NanoXAS beamline in the Swiss Light Source. The end stations should be available for a broad user community at Solaris in 2016. Copyright © 2015 John Wiley & Sons, Ltd.